2019
DOI: 10.1039/c9cp01759c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monomer deformation on the competition between two types of σ-holes in tetrel bonds

Abstract: Competition between two competing sites on a tetrel atom is explained by balance between structural deformation and σ-hole intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 115 publications
(115 reference statements)
1
17
0
Order By: Relevance
“…There is some prior confirmation of our observation here that formation of a noncovalent bond is sufficient incentive for a molecule to undergo substantial deformation so as to maximize this interaction, mainly in the context of tetrel and pnicogen bonds 107,108 and that this distortion can influence the preference of an incoming base for one σ-hole over another 109 . In the context of hypervalent molecules, ZF5, where Z represents a pnicogen atom, [110][111] takes on a trigonal bipyramid shape as a monomer, but then distorts into a square pyramid so as to accommodate an incoming nucleophile, at significant cost in terms of deformation energy.…”
Section: Survey Of Crystal Datasupporting
confidence: 78%
“…There is some prior confirmation of our observation here that formation of a noncovalent bond is sufficient incentive for a molecule to undergo substantial deformation so as to maximize this interaction, mainly in the context of tetrel and pnicogen bonds 107,108 and that this distortion can influence the preference of an incoming base for one σ-hole over another 109 . In the context of hypervalent molecules, ZF5, where Z represents a pnicogen atom, [110][111] takes on a trigonal bipyramid shape as a monomer, but then distorts into a square pyramid so as to accommodate an incoming nucleophile, at significant cost in terms of deformation energy.…”
Section: Survey Of Crystal Datasupporting
confidence: 78%
“…This observation is consistent with expectation in terms of the σ-hole model to explain the nature of these interactions [45] , [46] , [47] , [251] . It might be concluded that while to a first approximation, there is a general understanding of the mode of bonding leading to Se … O and related secondary bonding interactions, further investigations, such high-level crystallographic, including charge density studies and analysis [11] , [252] , [253] , along with reliable computational chemistry studies [254] , [255] , [256] are required in order to gain a more complete picture of Se … O interactions. Also of interest would be the determination, experimental and theoretical, of the energies of stabilisation provided by specific Se … O contacts.…”
Section: Overviewmentioning
confidence: 99%
“…As a second important difference, the normal tetravalency of the tetrel atom leads to a great deal of steric repulsions with any potential nucleophile. Earlier works [8f,h,22] have shown the crowded nature of the surrounding groups causes a good deal of geometric rearrangement in order to accommodate an additional ligand. Indeed, in some cases, this deformation can entirely alter the competition between different modes of bonding.…”
Section: Introductionmentioning
confidence: 99%